Potential role of electroencephalographic monitoring for diagnosis and treatment of local anesthetic systemic toxicity during general anesthesia: a case report - Ryo Wakabayashi; Seiichi Azuma; Saori Hayashi; Yuji Ueda; Masaki Iwakiri; Masaaki Asamoto; Kanji Uchida (JA Clinical Reports)
Abstract Background Local anesthetic systemic toxicity (LAST) is a rare but potentially life-threatening complication. Under general anesthesia, neurological signs are often masked, delaying diagnosis and increasing the risk of sudden cardiovascular collapse. Therefore, early detection methods are critically needed. Case presentation A 48-year-old male patient (height: 182 cm, weight: 98 kg) underwent resection of a mediastinal goiter. He received 10 mL of 4% lidocaine for topical airway anesthesia and 20 mL of 1% lidocaine with 1:100,000 epinephrine for chest wall anesthesia. Thirty minutes after airway anesthesia, continuous theta waves appeared on the frontal electroencephalogram (EEG), which were enhanced following chest wall anesthesia. These waves transitioned into a repeating pattern and evolved into sharp periodic discharges. After administering 150 mL of 20% lipid emulsion, the EEG normalized. Conclusions This case highlights that EEG monitoring during general anesthesia may facilitate the early detection of LAST and provide real-time feedback on treatment efficacy.